Barriers and facilitators to timely birth-dose vaccines in Kinshasa Province, the DRC: a qualitative study - Alix Boisson; Camille E. Morgan; Bruce Fried; Christopher M. Shea; Marcel Yotebieng; Patrick Ngimbi; Nana Mbonze; Kashamuka Mwandagalirwa; Pélagie Babakazo; Peyton Thompson (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background National vaccine policies across the world have successfully improved infant vaccine coverage, but birth-dose (BD) vaccine coverage remains low. Countries such as the Democratic Republic of the Congo (DRC) aim to include the hepatitis B birth-dose (HepB-BD) vaccine in their national immunization schedule. HepB-BD's short window for administration -- within 24 hours of delivery to prevent mother-to-child transmission -- adds to the complexity of streamlined and timely BD vaccines. This study aims to identify and understand barriers and facilitators to timely delivery of BD vaccine in Kinshasa Province, DRC, through individuals' accounts with different perspectives on the uptake of the BD vaccine in preparation for its future roll-out. # Methods We conducted semi-structured interviews in seven health facilities across Kinshasa Province from June to July 2021. We purposefully sampled health facilities from the provinces' five most prominent facility types---private, public, Catholic, Protestant, and not-for-profit. We interviewed decision-makers and/or providers from various levels of the health care continuum, including midwives, immunization staff, heads of maternity and immunizations, and vaccine officials at the health zone and the Programme Elargi de Vaccination (PEV) to understand administrative barriers to BD vaccines. We also conducted interviews with expectant mothers to elicit knowledge and perceptions about infant vaccines. # Results We interviewed 30 participants (16 informants and 14 expectant mothers). Interviewees were recruited from 7 health facilities, 2 health zones, and PEV. Data analysis was guided by the Consolidated Framework for Implementation Research (CFIR). Our analysis identified 13 constructs (2-3 per domain) related to the success of timely and streamlined BD vaccines. We found significant barriers within and across each domain; most notably, the multi-dose vials of existing BD vaccines determining when facility staff could vaccinate newborns, often resulting in untimely vaccinations; logistical concerns with regular national vaccine stockouts and ability to store vaccines; complex and unsynchronized vaccine fees across facilities; inadequate communication across delivery and vaccination wards; and limited and at times incorrect understanding of vaccines among mothers and other community members. # Conclusions Using the CFIR framework, this study integrated perspectives from facility informants and expectant mothers to inform national policy and implementation of the HepB-BD in DRC. These stakeholder-driven findings should guide the streamlining of timely BD vaccinations upon HepB-BD implementation.